Administrative Instruments for the Promotion of Technological Innovation in the Peruvian Financial Sector - Suárez Barcia, Lucía (2021)
This document strives to analyze the new approaches to regulatory supervision (innovation facilitators) that are being developed worldwide because of the fintech phenomenon, evaluating whether they would be beneficial for Perú, especially in relation to financial inclusion. For this reason, we have proceeded to a review of initiatives to promote fintech innovation worldwide, studying their characteristics. This analysis has a teleological nature of reviewing administrative supervision policies, grouping them into three large taxonomies: innovation centers, sandbox and others, such as innovation accelerators, studying in greater detail the sandboxes due to their relevance and potential impact. Specifically, the article explains the concept of sandbox, including the objectives for which they are designed, their main benefits and risks. Afterwards, the paper specifies the phases that these projects usually go through and their timelines. Two particular cases of sandbox are also described, the Mexican, which requires a «new model» license; and theIsraeli, focused on data. Subsequently, the potential benefits and challenges of applying this type of public policy in Peru are evaluated. Finally, a model is proposed for the country, aligned with the financial inclusion strategy, which allows the open participation of all types of entities, including those called fintech, for the greater benefit of society and the markets.